The opposable mind : how successful leaders win through integrative thinking - Martin, Roger L. (Boston : Harvard Business School Press, 2007)
A comprehensive guide for strengthening integrative thinking skills by drawing on different kinds of knowledge.
Choices, conflict, and the creative spark: the problem-solving power of integrative thinking -- No stomach for second-best: how integrative thinkers move beyond trade-offs -- Reality, resistance, and resolution: how integrative thinkers keep their options open -- Dancing through complexity: shaping resolutions by resisting simplification -- Mapping the mind: how thought circulates -- The construction project: imagining reality -- A leap of the mind: how integrative thinkers connect the dots -- A wealth of experience: using the past, inventing the future.
Includes bibliographical references (p. 193-198) and index.
Adult
Keywords: Contradiction; Decision making; Leadership -- Psychological aspects; Problem solving; Successful people -- Interviews; Thought and thinking; Decision making; Leadership -- Psychological aspects; Problem solving; Thought and thinking